2013
DOI: 10.11648/j.ijnfs.20130203.12
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Bacteriocin Produced by Lactobacillus Plantarum 29V and Strain′S Viability in Palm Kernel Oil

Abstract: Abstract:The present investigation reports the characterization of the bacteriocin produced by the probiotic strain Lactobacillus plantarum 29V isolated from raw cow milk in the Western's highlands of Cameroon, as well as the viability of this strain in the palm kernel oil. The antimicrobial compound synthesized by Lactobacillus plantarum 29V was sensitive to some proteolytic enzymes. It showed remarkable stability at high temperatures and in the presence of organic solvents, detergents and surfactants. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Enterococcus faecium (LUM35, LUM38 and SOF45) strains showed the highest antimicrobial activity against food borne pathogens. Similar results were also reported with Enterococcus faecium (Araújo and Ferreira, 2013;Francois et al, 2013), also they observed the antimicrobial activity of Enterococcus faecium and Lb. plantarum against spoilage.…”
Section: Antibacterial Activitysupporting
confidence: 89%
“…Enterococcus faecium (LUM35, LUM38 and SOF45) strains showed the highest antimicrobial activity against food borne pathogens. Similar results were also reported with Enterococcus faecium (Araújo and Ferreira, 2013;Francois et al, 2013), also they observed the antimicrobial activity of Enterococcus faecium and Lb. plantarum against spoilage.…”
Section: Antibacterial Activitysupporting
confidence: 89%
“…18,21 Moreover, the low inhibitory effect of CeO 2 NPs on E. coli O157:H7 and that of both NPs on S. aureus in the monoculture tests was substantially enhanced by coculture with L. plantarum. As pointed out by François et al 15 and Sharif et al, 20 L. plantarum can effectively inhibit the growth of E. coli and S. aureus. Similarly, a Lactobacillus species was shown to be effective against S. aureus in two other studies.…”
mentioning
confidence: 87%
“…[14][15][16] Of these metabolites, bacteriocins are of particular interest because there have been several reports demonstrating their antimicrobial efficiency across a broad spectrum of microbes. [17][18][19] Although many bacteria can produce bacteriocins, L. plantarum is chosen in this study due to its Generally Regarded As Safe status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations